2020
DOI: 10.1101/2020.08.24.263970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Piwis with Ago-like functions silence somatic genes at the chromatin level

Abstract: Most sRNA biogenesis mechanisms involve either RNAseIII cleavage or ping-pong amplification by different Piwi proteins harboring slicer activity. Here, we follow thequestion why the mechanism of transgene-induced silencing in the ciliate Paramecium needs both Dicer activity and two Ptiwi proteins. This pathway involves primary siRNAs produced from non-translatable transgenes and secondary siRNAs from endogenous remote loci. Our data does not indicate any signatures from ping-pongamplification but Dicer clea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…A feeding-induced siRNA-based RNAi pathway has been validated as a tool for gene knock-down in the non-photo-endosymbiotic ciliate, P. tetraurelia [33,34,36,48]. To establish the presence of a comparable pathway in P. bursaria, combined genomic and transcriptomic analyses were employed to identify putative homologues for all previously characterized P. tetraurelia RNAi protein components [33,45] (figure 1). We found that P. bursaria encodes a total of five Dicer or Dicer-like endonucleases (Dcr1, Dcr2/3-electronic supplementary material, dataset S1; Dcl1/2, Dcl3/4 and Dcl5-electronic supplementary material, dataset S2), three RdRPs (Rdr1/4, Rdr2 and Rdr3-electronic supplementary material, dataset S3), six AGO-Piwi components (PiwiA1, PiwiA2, PiwiB, PiwiC1, PiwiC2 and PiwiDelectronic supplementary material, dataset S4), a single Paramecium-specific Pds1 (Pds1-electronic supplementary material, dataset S5), and two nucleotidyl transferase (Cid1/3 and Cid2-electronic supplementary material, dataset S6) genes.…”
Section: Bioinformatic Identification Of a Putative Rnai Pathway In P Bursariamentioning
confidence: 99%
See 1 more Smart Citation
“…A feeding-induced siRNA-based RNAi pathway has been validated as a tool for gene knock-down in the non-photo-endosymbiotic ciliate, P. tetraurelia [33,34,36,48]. To establish the presence of a comparable pathway in P. bursaria, combined genomic and transcriptomic analyses were employed to identify putative homologues for all previously characterized P. tetraurelia RNAi protein components [33,45] (figure 1). We found that P. bursaria encodes a total of five Dicer or Dicer-like endonucleases (Dcr1, Dcr2/3-electronic supplementary material, dataset S1; Dcl1/2, Dcl3/4 and Dcl5-electronic supplementary material, dataset S2), three RdRPs (Rdr1/4, Rdr2 and Rdr3-electronic supplementary material, dataset S3), six AGO-Piwi components (PiwiA1, PiwiA2, PiwiB, PiwiC1, PiwiC2 and PiwiDelectronic supplementary material, dataset S4), a single Paramecium-specific Pds1 (Pds1-electronic supplementary material, dataset S5), and two nucleotidyl transferase (Cid1/3 and Cid2-electronic supplementary material, dataset S6) genes.…”
Section: Bioinformatic Identification Of a Putative Rnai Pathway In P Bursariamentioning
confidence: 99%
“…In ciliates, multiple whole genome duplication (WGD) events have led to the rapid expansion of gene families encoding RNAi components [38][39][40], resulting in a subsequent diversification of protein function. Example functions include transposon elimination, nuclear rearrangement and transcriptional regulation [32,35,[41][42][43][44][45]. Elegant investigation of the non-photo-endosymbiotic model system, Paramecium tetraurelia, has identified three distinct classes of RNAi pathway in Paramecium.…”
Section: Introductionmentioning
confidence: 99%
“…tetraurelia RNAi protein components 33,45 (Figure 1). We found that P. bursaria encodes a total of five Dicer or Dicer-like endonucleases (Dcr1, Dcr2/3 -Dataset S1; Dcl1/2, Dcl3/4 and Dcl5 -Dataset S2), three RdRPs (Rdr1/4, Rdr2 and Rdr3 -Dataset S3), six AGO-Piwi components (PiwiA1, PiwiA2, PiwiB, PiwiC1, PiwiC2 and PiwiD-Dataset S4), a single Paramecium-specific Pds1 (Pds1 -Dataset S5), and two nucleotidyl transferase (Cid1/3 and Cid2 -Dataset S6)…”
Section: Identifying a Putative Rnai Pathway In P Bursariamentioning
confidence: 99%
“…A feeding-induced siRNA-based RNAi pathway has been validated as a tool for gene knock-down in the non-photo-endosymbiotic ciliate, P. tetraurelia 33,34,36,48 . To establish the presence of a comparable pathway in P. bursaria, combined genomic-and transcriptomic-analyses were employed to identify putative homologues for all previously characterised P. tetraurelia RNAi protein components 33,45 ( Figure 1). We found that P. bursaria encodes a total of five Dicer or Dicer-like endonucleases (Dcr1, Dcr2/3 -Dataset S1; Dcl1/2, Dcl3/4 and Dcl5 -Dataset S2), three RdRPs (Rdr1/4, Rdr2 and Rdr3 -Dataset S3), six AGO-Piwi components (PiwiA1, PiwiA2, PiwiB, PiwiC1, PiwiC2 and PiwiD-Dataset S4), a single Paramecium-specific Pds1 (Pds1 -Dataset S5), and two nucleotidyl transferase (Cid1/3 and Cid2 -Dataset S6) genes.…”
Section: Bioinformatic Identification Of a Putative Rnai Pathway In Pmentioning
confidence: 99%
“…For antibody against P. tetraurelia RBP1, the peptide SPHYTSHTNSPSPSYRSS-C was used for rabbit immunisation. Purification and testing of specificity by Western blots and immunostaining was carried out as described recently [18]. Since there are some amino acid differences in the N-terminal tail of the Paramecium H3P1 to Human H3 (Suppl.…”
Section: Antibodiesmentioning
confidence: 99%